Getting To Know the School Library Media Specialist. Instructional Resource No. 25 - DeGroff, Linda; National Reading Research Center, Athens, GA.; National Reading Research Center, College Park, MD. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1996)
This booklet is intended to help spread the word about the library and the librarian's role. It discusses the three interwoven roles of the school library media specialist--the role of information specialists (the "traditional" role); the role of library-media teachers in which they advance the goals of the school's literacy and general educational programs; and the role of instructional consultants in which they work in concert with classroom teachers to assure that library and research skills are integrated into the content areas rather than taught in isolation. A 7-item list of journal articles on the school library and the role of the library media specialist, and an 11-item list of books and journal articles on teachers and library media specialists working together are attached. (RS)
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Contract Number: 117A20007.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Elementary Secondary Education; Librarian Teacher Cooperation; Librarians; Library Role; Library Services; Library Skills; Media Specialists; School Libraries; Role Delineation; Guides, Non-Classroom.